2022
DOI: 10.1111/ijd.16213
|View full text |Cite
|
Sign up to set email alerts
|

Clinical decision‐making bias in darker skin types: a prospective survey study identifying diagnostic bias in decision to biopsy

Abstract: Correspondence e252evaluation and decision making in darker skin. Conversely, lower likelihood to biopsy malignancies is of significant concern as it could contribute to advanced staging at initial diagnosis in SOC patients. Further investigation around bias in clinical decision making is essential as we strive for health equity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Our results are congruent with a 2022 study which identified that dermatology residents are more likely to biopsy nonmalignant lesions than malignant lesions of darker skin. 10 While the national push for improved recognition and treatment for cutaneous diseases in darker skin types has improved for the average patient, such efforts may not yet translate into improved health equity nor health outcomes with regard to skin cancer. It thus remains of concern that some lesions may be misdiagnosed or delayed in diagnosis, yielding higher risk for morbidity and mortality.…”
Section: Skinmentioning
confidence: 99%
“…Our results are congruent with a 2022 study which identified that dermatology residents are more likely to biopsy nonmalignant lesions than malignant lesions of darker skin. 10 While the national push for improved recognition and treatment for cutaneous diseases in darker skin types has improved for the average patient, such efforts may not yet translate into improved health equity nor health outcomes with regard to skin cancer. It thus remains of concern that some lesions may be misdiagnosed or delayed in diagnosis, yielding higher risk for morbidity and mortality.…”
Section: Skinmentioning
confidence: 99%